Rozwiązania metodologiczne w badaniach nad rasizmem i ksenofobią u dzieci – analiza przeglądowa - Dobosz, Dagmara; Gierczyk, Marcin (Chowanna, 2019)
The article is a review of research on racist feelings, attitudes and behaviours in relation to children. The authors focus on research tools used, including Clark Doll Test, Preschool Attitude Measure or Sticker Test. The analyses have shown that the phenomenon of racism and xenophobia is being increasingly raised in the scientific discourse in the context of this age group. In addition, it is emphasized that the concepts of race, religion or social class as key determinants of the place of man in society are unethical and immoral.